PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL PEMBELAJARAN TEMATIK DI KELAS IV SD - Sariwati, Sariwati; Margiati, KY.; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to analyze the presence or absence of the effect of applying the model of Problem Based Learning for learning outcomes and analyze how much influence the Problem Based Learning on student learning outcomes in thematic learning in fourth grade Elementary School 39 Pontianak City. This study used an experimental method to formPre-Experimental Design kind of one group pretest-posttest design. The population around the fourth grade students of State Elementary School 39 Pontianak City which consists of 96 students,Sampling is purposive sampling technique, namely SDN 39 IVA class Pontianak City.Techniques used in the data collection is the measurement of the data collection tool that is used is an objective written test form. Based on the result the average pre-test students 67.75 and an average yield of 76.57 students' post-test. This suggests improving student learning outcomes in applying the model of problem-based learning. After the t test obtained t 8.83 while ttable with db = 28-1 = 27 and the significant level(= 5% is 1.703, it turns out t ≥ ttable or 8.83 ≥ 1,703, which means a significant influence on the application of the model Problem Based Learning. From the calculation of effect size (ES) ES obtained at 0.79 with a relatively high criteria. This means that the application of the Problem Based Learning provides high impact on student learning outcomes in thematic learning in fourth grade Elementary School 39 Pontianak City. Keywords: Effects, Model Problem Based Learning, learning outcomes, Thematic